Conduction system pacing in everyday clinical practice: EHRA physician survey. Issue 2 (22nd November 2022) - Kircanski, Bratislav; Boveda, Serge; Prinzen, Frits; Sorgente, Antonio; Anic, Ante; Conte, Giulio; Burri, Haran
Abstract: With the increasing interest in conduction system pacing (CSP) over the last few years and the inclusion of this treatment modality in the current guidelines, our aim was to provide a snapshot of current practice across Europe. An online questionnaire was sent to physicians participating in the European Heart Rhythm Association research network as well as to national societies and over social media. Data on previous experience with CSP, current indications, preferred tools, unmet needs, and perceptions for the future are reported and discussed.